2016
DOI: 10.1007/s00421-016-3392-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aortic root size on left ventricular afterload and stroke volume

Abstract: Larger aortic root size is an independent determinant of EA and SV. This association was heterogeneous and stronger in patients on CCB therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…However, a fully personalized model would not be possible, since this would require us to obtain numerous noninvasive and invasive measurements for every individual. Since CO is known to be particularly dependent on arterial geometry measurements [73], individualized CO prediction still remains a challenge.…”
Section: A Limitationsmentioning
confidence: 99%
“…However, a fully personalized model would not be possible, since this would require us to obtain numerous noninvasive and invasive measurements for every individual. Since CO is known to be particularly dependent on arterial geometry measurements [73], individualized CO prediction still remains a challenge.…”
Section: A Limitationsmentioning
confidence: 99%
“…Aortic root aneurysm is characterized by slower blood flow and endothelial dysfunction, which cause thrombi to form easily, and aortic root size is an independent determinant of larger stroke volume. 7 Therefore, we speculate that the emboli of the basilar artery might originate from aortic root aneurysm.…”
Section: Discussionmentioning
confidence: 90%
“…4 The authors suggested that dilation of the AoR in elderly and hypertensive patients may be favorable, possibly by mitigating the adverse impact of concomitant aortic wall stiffening. 29 Thus, simultaneous studies of AoR dilation and arterial stiffness in transplant patients are justified.…”
Section: Discussionmentioning
confidence: 99%